Institutional and Technological Optimization to Support the Sustainability of Young Farmers' Businesses - Suardi Bakri; Annisa Risdianika Putri; Kisman Awaluddin Arsyad; Muhammad Azhar; Helda Ibrahim (Unit Penelitian dan Pengabdian Masyarakat Politeknik Pembangunan Pertanian Gowa, 2026)
In an effort to strengthen the independence and sustainability of young farmers' businesses, the Indonesian government has implemented various programs, one of which is the Youth Entrepreneurship and Employment Support Services (YESS) program through several simultaneous interventions, including fostering agricultural businesses run by young farmers. Business sustainability after program intervention is sometimes an issue. Therefore, this study aims to assess the level of sustainability using benchmarks for approaches to increasing revenue, production, and product diversification as well as formulate strategies for the sustainability of young farmers' businesses after program intervention. The research was conducted in Bulukumba Regency, South Sulawesi Province, with a sample of 30 young farmers who were beneficiaries of the program, supported by secondary data from program implementers at the provincial, Project Implementation Unit, and regency levels, as well as the District Implementation Team. Data was collected through interviews, field observations, and documentation. Data analysis was conducted using SWOT analysis. The results of the study show that program interventions, especially capital assistance programs, contribute positively to capital strengthening, business capacity building, and business diversification. On the other hand, there are weaknesses in business management, innovation, and market access. The SWOT analysis results place young farmers' businesses in the aggressive-adaptive strategy quadrant with the main strategy recommendations being optimization of institutional support, utilization of digital technology in marketing, improvement of managerial and technical capacity through training, and business diversification to deal with external risks. This shows that the YESS Program intervention supports the sustainability of young farmers' businesses.